2015
DOI: 10.1186/s12902-015-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone (GH) dose-dependent IGF-I response relates to pubertal height gain

Abstract: BackgroundResponsiveness to GH treatment can be estimated by both growth and ∆IGF-I. The primary aim of the present study was to investigate if mimicking the physiological increase during puberty in GH secretion, by using a higher GH dose could lead to pubertal IGFs in short children with low GH secretion. The secondary aim was to explore the relationship between IGF-I, IGFBP-3 and the IGF-I/IGFBP-3 ratio and gain in height.MethodsA multicentre, randomized, clinical trial (TRN88-177) in 104 children (90 boys),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The patients with acquired GHD were also taller and had a higher BMI SDS at diagnosis than those with non-acquired GHD. Serum IGF-I SDS increased after treatment initiation in all groups, but, consistent with other reports (10,14,23), was found to be independent of treatment duration, with median values remaining stable from six months after the start of treatment until the final evaluation, although most reports, with the exception of three studies concerning patients with a treatment duration of three to five years (15,16,17), described findings for the first one to two years of treatment only (9,10,11,12,13,14).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The patients with acquired GHD were also taller and had a higher BMI SDS at diagnosis than those with non-acquired GHD. Serum IGF-I SDS increased after treatment initiation in all groups, but, consistent with other reports (10,14,23), was found to be independent of treatment duration, with median values remaining stable from six months after the start of treatment until the final evaluation, although most reports, with the exception of three studies concerning patients with a treatment duration of three to five years (15,16,17), described findings for the first one to two years of treatment only (9,10,11,12,13,14).…”
Section: Discussionsupporting
confidence: 88%
“…To date, only a few studies have assessed the value of serum IGF-I SDS monitoring for exploring the variability of serum IGF-I SDS during GH treatment in children with GH deficiency (9,10,11,12,13,14,15,17). Previous studies have reported considerable individual biological variation of serum IGF-I SDS, as also found in this study, for all ages and treatment durations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…GH is derived from the somatotrophs in the anterior pituitary that induces the liver to produce insulin growth factor 1 which, together with sex hormones, induces the growth of bone and muscle mass during puberty (Devesa, Almengló, & Devesa, ). Also, GH accelerates cartilage growth, intramembranous bone growth, including the suture as well as cartilage development (Lundberg, Kriström, Jonsson, & Albertsson‐Wikland, ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the severity of the IGHD, some time may be needed for dose escalation. Basically, a dose that is high enough and within label to give a substantial short‐time IGF‐I increment and catch‐up growth should be used, as the greatest growth response in relation to the dose is seen during the first year on GH treatment.…”
Section: Introductionmentioning
confidence: 99%